2021
DOI: 10.1371/journal.pone.0244468
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide capture sequencing of the SARS-CoV-2 genome and subgenomic fragments from COVID-19 individuals

Abstract: The newly emerged and rapidly spreading SARS-CoV-2 causes coronavirus disease 2019 (COVID-19). To facilitate a deeper understanding of the viral biology we developed a capture sequencing methodology to generate SARS-CoV-2 genomic and transcriptome sequences from infected patients. We utilized an oligonucleotide probe-set representing the full-length genome to obtain both genomic and transcriptome (subgenomic open reading frames [ORFs]) sequences from 45 SARS-CoV-2 clinical samples with varying viral titers. Fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Previous studies have reported successful genome recovery in samples with low Ct values (<25) ( 28 , 29 ). Our findings indicated that there was no significant correlation between genome coverage and Ct value when using either version of the ARTIC primers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported successful genome recovery in samples with low Ct values (<25) ( 28 , 29 ). Our findings indicated that there was no significant correlation between genome coverage and Ct value when using either version of the ARTIC primers.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated that there was no significant correlation between genome coverage and Ct value when using either version of the ARTIC primers. Genomes with >95% coverage were recovered from samples with higher Ct values ( 24 – 29 ), and the differences observed could be either due to sample-to-sample variation or batch processing. Therefore, when using the optimized V4 primers, genome completeness (>95%) can be expected for samples with a wide Ct value range ( 14 – 29 ) regardless of the lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Shotgun sequencing requires no prior knowledge of the targeted viral genome 15 but is limited by requirements for a high viral load and a higher sequencing depth. Hybridization approaches target genomic regions of interest by using biotinylated probes and ensure a more complete profiling of regions of interest 16 . Since the initial release of the ARTIC SARS-CoV-2 sequencing protocol early in the outbreak (Jan 22, 2020, https://artic.network/ncov-2019 ), amplicon-based sequencing has become the primary choice for many labs around the world and numerous commercial kits are also available 14 .…”
Section: Introductionmentioning
confidence: 99%
“…(2) A genotyping PCR panel could be very useful in resource-limited settings, since sequencing is not done at the same level in all locations/countries, and many laboratories do not have the infrastructure or expertise to perform sequencing ( 51 ). (3) Obtaining whole genome sequence data from clinical samples is very much dependent on viral load; reported PCR Cq cutoffs for obtaining full-length genome sequences range from ~25–33 ( 52 , 53 ). A PCR panel could fill this gap by providing genotype information for numerous samples that cannot be sequenced due to low viral load as reflected by high Cq values ( 31 ).…”
Section: Discussionmentioning
confidence: 99%